Embodied Cognition Comes of Age: A Processing Advantage for Action Words Is Modulated by Aging and the Task - Garcia-Serrano, A (American Psychological Association, 2024)
Processing action words (e.g., fork, throw) engages neurocognitive motor representations, consistent with embodied cognition principles. Despite age-related neurocognitive changes that could affect action words, and a rapidly aging population, the impact of healthy aging on action-word processing is poorly understood. Previous research suggests that in lexical tasks demanding semantic access, such as picture naming, higher motor-relatedness can enhance performance (e.g., fork vs. pier)—particularly in older adults, perhaps due to the age-related relative sparing of motor-semantic circuitry, which can support action words. However, motor-relatedness was recently found to affect performance in younger but not older adults in lexical decision. We hypothesized this was due to decreased semantic access in this task, especially in older adults. Here we tested effects of motor-relatedness on 2,174 words in younger and older adults not only in lexical decision but also in reading aloud, in which semantic access is minimal. Mixed-effects regression, controlling for phonological, lexical, and semantic variables, yielded results consistent with our predictions. In lexical decision, younger adults were faster and more accurate at words with higher-motor relatedness, whereas older adults showed no motor-relatedness effects. In reading aloud, neither age group showed such effects. Multiple sensitivity analyses demonstrated that the patternswere robust. Altogether, whereas previous research indicates that in lexical tasks demanding semantic access, higher motor-relatedness can enhance performance, especially in older adults, evidence nowsuggests that such effects are attenuatedwith decreased semantic access,which in turn depends on the task as well as aging itself. © 2024 American Psychological Association